Напрямки взаємодії та координації діяльності правоохоронних органів на регіональному рівні - Русецький, А. А.; Rusetskyi, A. A. (Європейські перспективи. - 2019. - № 1. – С. 74-79, 2019)
Наведено теоретичне узагальнення та нове вирішення наукового завдання, що полягає у визначенні напрямків взаємодії та координації діяльності правоохоронних органів на регіональному рівні. Констатовано, що забезпечення прав та свобод людини і громадянина, а також їх захист, апріорі є одним із найважливіших напрямків взаємодії правоохоронних органів на регіональному рівні. Зазначено, що сутність забезпечення законності, як напрямку взаємодії та координації правоохоронних органів на регіональному рівні полягає у тому, що спільна діяльність зазначених органів у переважній більшості випадків спрямовується на те, щоб створити такий стан функціонування суспільних відносин на регіональному рівні, за якого всі фізичні та юридичні особи, а також органи державної влади, будуть неухильно дотримуватись норм чинного законодавства України при здійсненні своєї діяльності.

In the article, on the basis of the analysis of scientifi c views of scientists and the current legislation of Ukraine, the theoretical generalization and a new solution of the scientifi c problem, which is to determine the directions of interaction and coordination of the activity of law enforcement bodies at the regional level are given. It was stated that ensuring the rights and freedoms of man and citizen, as well as their protection, is a priori one of the most important directions of interaction of law enforcement bodies at the regional level. This is explained fi rst and foremost by the purpose of the existence of the lawenforcement bodies of Ukraine, because, in carrying out joint activities, law enforcement agencies fi rst of all take on the responsibility to ensure the protection of human rights and freedoms, as well as to create all the necessary conditions for each person to feel protected and could fully realize the constitutional guarantees guaranteed by it. It is noted that the essence of ensuring the lawfulness, as a direction of interaction and coordination of law enforcement bodies at the regional level, is that the joint activity of these bodies in the vast majority of cases is aimed at creating a state of functioning of social relations at the regional level in which all physical and legal entities, as well as state authorities, will strictly adhere to the norms of the current legislation of Ukraine in the course of its activities. The emphasis is placed on the fact that the maintenance of law and order is important in terms of creating such a state of social legal relations, in which these relationships can be characterized by such qualities as: stability, orderliness and regulation. A characteristic feature of the rule of law as a direction of interaction and coordination of law enforcement agencies at the regional level is that the law and order in its essence is volitional, and its achievements, in the context of the submitted scientifi c work, directly depend on the quality of the joint work of law enforcement bodies at the regional level.

Приведены теоретическое обобщение и новое решение научной задачи, заключающейся в определении направлений взаимодействия и координации деятельности правоохранительных органов на региональном уровне. Констатировано, что обеспечение прав и свобод человека и гражданина, а также их защита априори является одним из важнейших направлений взаимодействия правоохранительных органов на региональном уровне. Отмечено, что сущность обеспечения законности как направления взаимодействия и координации правоохранительных органов на региональном уровне заключается в том, что совместная деятельность указанных органов в подавляющем большинстве случаев направляется на то, чтобы создать такое состояние функционирования общественных отношений на региональном уровне, при котором все физические и юридические лица, а также органы государственной власти, будут неукоснительно соблюдать нормы действующего законодательства Украины при осуществлении своей деятельности.
Русецький, А. А. Напрямки взаємодії та координації діяльності правоохоронних органів на регіональному рівні / Русецький Анатолій Анатолійович // Європейські перспективи. - 2019. - № 1. – С. 74-79.
Keywords: Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; правоохоронні органи; law enforcement agencies; правоохранительные органы; взаємодія; interaction; взаимодействие; координація; coordination; координация; регіональний рівень; regional level; региональный уровень; правопорядок; law and order; законність; legality; законность; права та свободи людини і громадянина; human and citizen rights and freedoms; права и свободы человека и гражданина